Intestinal Adenocarcinoma Arising from a Mature Cystic Teratoma - King Man Wan; Forough Foroughi; Rajni Bansal; Martin K. Oehler (Hindawi Limited, 2019)
Mature cystic teratomas are the most common ovarian germ cell tumour and account for 10-20% of all ovarian neoplasms. Malignant transformation of mature cystic teratomas is rare and has an incidence rate of less than 1%. The most common malignancy are squamous cell carcinomas. Here we present the case of an intestinal adenocarcinoma which is an exceedingly rare malignant entity arising within a mature cystic teratoma. Clinical presentation, imaging and histopathological diagnosis are discussed and previously presented cases in the literature reviewed.